Antioxidant capacity and total phenols of wild poinsettia (Euphorbia heterophylla) as potential tea infusion product - Destryana, R Amilia; Fajarianingtyas, Dyah Ayu; Wibisono, Aryo; Witono, Yuli; Taruna, Iwan; Belgis, Maria (Penerbit Universiti Kebangsaan Malaysia, 2022)
The use of wild poinsettia (Euphorbia heterophylla) is known as a traditional medicinal ingredient. The potential of this plant is the latex which can be used as a protease enzyme and the leaves can be used as herbal tea or tea infusion. To provide the potential of dried wild poinsettia, the total phenols and antioxidant capacity were measured by the Folin-Ciocalteu method, and the antioxidant capacity was assessed by DPPH assays. Phytochemical screening of dried wild poinsettia leaves which were dried at different temperatures (50 ºC & 60 ºC) and drying times (2, 3, & 4 h) showed total phenols and antioxidant capacity which have potential health properties and benefits on human health, such as anti-inflammatory, antihypertensive, anticancer, and as antimicrobial agents. The antioxidant activity values varied from 40.07 – 56.50%, and the highest values (56.50 ± 2.35) were obtained at 50 ºC for 2 h of the drying process. Total phenols in those tea leave varied from 11.47 – 13.41 mg GAE/g. The highest phenol content (13.41 ± 0.30 mg GAE/g) was found in dried tea leaves which were dried at 60 ºC for 4 h of the drying process. According to the result, the significant inverse linear correlation (p<0.05) was confirmed between treatments of drying duration, while not in the temperature. Generally, these dried leaves have a high antioxidant capacity and total phenol content and may be an important food source as tea infused with antioxidant phenolic compounds to prevent oxidative stress diseases.